Isolation of Apoplastic Fluid from Woody Plant Leaves: Grapevine and Coffee as a Case Study - Figueiredo, A. (2022)
Proteomics is one of the key approaches to understand plant cell physiology involving the regulation of expression of many genes and metabolite production. Technical advances allowed a deeper characterization of plant proteomes, highlighting the need to study cellular compartments. The apoplast is the cellular compartment external to the plasma membrane including the cell wall, where a broad range of processes take place including intercellular signaling, metabolite transport, and plant–microbe interactions. Due to the fragile nature of leaf tissues, it is a challenge to obtain apoplastic fluids from leaves while maintaining cell integrity, which is particularly true for woody plants. Here, we describe the vacuum infiltrationcentrifugation (VIC) method for the extraction of the apoplastic fluid compatible with high-throughput proteomic approaches and biochemical analysis from different woody plants